Immersed Boundary-Lattice Boltzmann Coupling Scheme for Fluid-Structure Interaction with Flexible Boundary (Communications in Computational Physics, 2020)
Coupling the immersed boundary (IB) method and the lattice Boltzmann(LB) method might be a promising approach to simulate fluid-structure interaction(FSI) problems with flexible structures and complex boundaries, because the formeris a general simulation method for FSIs in biological systems, the latter is an efficientscheme for fluid flow simulations, and both of them work on regular Cartesian grids.In this paper an IB-LB coupling scheme is proposed and its feasibility is verified. Thescheme is suitable for FSI problems concerning rapid flexible boundary motion and alarge pressure gradient across the boundary. We first analyze the respective concepts,formulae and advantages of the IB and LB methods, and then explain the couplingstrategy and detailed implementation procedures. To verify the effectiveness and accuracy,FSI problems arising from the relaxation of a distorted balloon immersed in aviscous fluid, an unsteady wake flow caused by an impulsively started circular cylinderat Reynolds number 9500, and an unsteady vortex shedding flow past a suddenlystarted rotating circular cylinder at Reynolds number 1000 are simulated. The firstexample is a benchmark case for flexible boundary FSI with a large pressure gradientacross the boundary, the second is a fixed complex boundary problem, and the third isa typical moving boundary example. The results are in good agreement with the analyticaland existing numerical data. It is shown that the proposed scheme is capable ofmodeling flexible boundary and complex boundary problems at a second-order spatialconvergence; the volume leakage defect of the conventional IB method has been remediedby using a new method of introducing the unsteady and non-uniform externalforce; and the LB method makes the IB method simulation simpler and more efficient.